Effect of irrigation protocols on root canal wall after post preparation: a micro-CT and microhardness study - de Rosatto, Camila Maria Peres; Ferraz, Danilo Cassiano [UNESP]; Oliveira, Lilian Vieira; Soares, Priscilla Barbosa Ferreira; Soares, Carlos José; Tanomaru-Filho, Mario [UNESP]; Moura, Camilla Christian Gomes (FapUNIFESP (SciELO), 2021)
The aim of this study was to investigate the effects of different post space irrigation protocols for removing residual filling material from dentin walls, by using microcomputed tomography (micro-CT), and the influence of these protocols on dentin microhardness. Bovine incisors (n = 35) were filled with the single-cone technique and MTA Fillapex (Angelus, Londrina, PR, Brazil). Post space preparation (PSP) was performed 7 days after filling, using the Odous Touch electrical system (Odous De Deus Ind. e Com., Belo Horizonte, MG, Brazil), followed by post space irrigation using manual irrigation, passive ultrasonic irrigation, or Easy Clean, together with 2.5% sodium hypochlorite (NaOCl), or with 2.5% NaOCl and 17% EDTA (NaOCl/EDTA). Micro-CT scans were performed at three time points. The residual filling material was evaluated at three levels: cervical, middle and apical. The Knoop test was measured with four indentations around the canal lumen at three dentin depths: X (100 μm), Y (200 μm) and Z (400 μm). Statistical analysis was performed using ANOVA (p < 0.05). The effects of the activation method (p < 0.001), and the root level (p = 0.013), as well as the interaction between the irrigant and the activation method (p = 0.041), led to different percentages of residual filling material. Lower amounts of residual filling material were observed at the cervical versus the middle and apical levels (p < 0.05). No significant differences were observed in dentin microhardness (p > 0.05). The best removal of the residual filling material was performed using the Easy Clean tip and NaOCl/EDTA, regardless of the activation methods
Keywords: Hardness tests; Root canal irrigants; X-ray microtomography